Biological control of Leptosphaeria maculans on Brassica napus and quantification of the microbes in planta using qPCR - Cholerton, Linda Jane (2015)
Brassica napus is a commercially important crop worldwide and its use is quickly increasing due to its beneficial oil products and biofuel demands. Yield can be lost through infection by a fungal pathogen, Leptosphaeria maculans, the causal agent of stem canker (blackleg). An early indication of the presence of stem canker is a lesion (leaf spot) on the cotyledons or early leaves. The leaf spot stage of the disease was used in this work to ascertain if biological control agents applied both individually and in combination decreased the lesion area and also to quantify the amount of L. maculans DNA present using quantitative polymerase chain reaction (qPCR). The natural production of antibiotics by some bacteria is a commonly found form of antagonistic biological control. Bacillus amyloliquefaciens and Pseudomonas chlororaphis spp. aureofaciens 30.84 evaluated in this work both produce antibiotics and were assayed for their ability to provide control of Leptosphaeria maculans. Known active strains and field isolates of Bacillus and Pseudomonas were tested as potential biocontrol agents in vitro and then used in in planta assays. The in planta assays using bacterial isolates applied individually indicated that all the bacteria gave statistically significant control of L. maculans at the leaf spot stage. Those isolates with highest activity were further evaluated in combination, to determine if improved control of leaf spot occurred. Firstly, however, it was important to confirm the two bacteria would be compatible and antibiotics would be produced. To this aim, an in vitro assay using mutant Chromobacterium violaceum confirmed Pseudomonas chlororaphis spp. aureofaciens upregulated antibiotic production using acyl-homoserine lactones, signalling molecules. Consequently, it was vital that the Bacillus applied with it did not produce lactonase which would denature these molecules. PCR was used to confirm the enzyme was not present. It was, however, shown using in planta assays that combinations of Bacillus and Pseudomonas did not halt the infection or growth of L. maculans, but appeared to lead to increased lesion size. Colonisation of the cotyledons by the bacterial biological control agents applied onto the cotyledons was monitored by washing recovery, serial dilution, plating and colony counting along with qPCR of the DNA. All bacteria colonised successfully when applied individually. However, the populations decreased from the quantity at time zero when they were applied in combination, indicating they were unable to colonise the cotyledons successfully under those circumstances. To quantify Leptosphaeria infection, the concentration of ergosterol, a fungal sterol, was quantified to measure the colonisation of cotyledons. Concentrations were assessed using high performance liquid chromatography (HPLC). This assay was not successful no free ergosterol could be detected. This was probably due to L. maculans either having small amounts of ergosterol in its cell membranes, or having most of the ergosterol esterfied and unsuitable for quantification using this method. Polymerase chain reaction (PCR) was used to ascertain the presence of fungal hyphae within asymptomatic regions of cotyledons. It was found that the fungal DNA was detected within all areas of the cotyledon irrespective of whether the leaf spot could be seen. This result highlights the unreliability of the common method of visually assessing the presence and/or severity of L. maculans infection using leaf spot area. To monitor the populations of bacteria and the fungus in real time, DNA was extracted from the cotyledons and quantified using quantitative PCR (qPCR). The amount of L. maculans DNA isolated decreased when the BCAs were applied individually, and increased when the BCAs were applied in combination (when compared with the amount isolated from the control cotyledons). These results confirmed earlier, non-molecular assessments. To provide a benchmark for biocontrol activity, fungicides used in the control of leaf spot on oilseed rape were tested under the standard experimental conditions. Whilst control was obtained, it was not as effective as when used in the field, probably due to the formulations being optimised for field conditions. Fungicides targeted at wheat pathogens were also tested for control against L. maculans. Field application rates of these fungicides were not successful, as all damaged the epidermis of the cotyledon, resulting in death of the plant. Application of ¼ field rate still induced epidermal damage in all cotyledons except those sprayed with Q8Y78 (now called Refinzar®), where a necrotic lesion could be seen without pycnidia, at day 15 after inoculation.